Terapia de ondas de choque y plasma rico en plaquetas ozonizadas en el tratamiento de entesopatías del músculo interosseus III - Duarte Pires, Eugenia (2020)
There is scientific evidence to validate the positive metabolic effects in the association of ozonized PRP intralesional application and extracorporous shock waves on soft tissues of sports horses. The main objective of this study was to compare the effectiveness effects from the association\nof both therapies in the treatment of lesions of the proximal third of the suspensory ligament in\nsports horses, with the effectiveness obtained from both independently applied therapies; evaluating and documenting the clinical and ultrasound progression of this pathology and the\nresults obtained from each treatment separately and those obtained in the group treated with both therapies.\nForty seven adult jumping horses with clinical and ultrasound diagnosis of M. interosseus III desmitis and/or enthesopathy were selected. None of these animals had received prior\ntreatment for such a pathology. The total number of horses was divided into three groups of similar size and each groups was\ntreated as previously determined: - Group 1: 15 equines treated with 3 applications of ozonized PRP with 10-day interval\nbetween treatments.\n-Group 2: 15 equines treated with 3 sections of Shock Wave with 10-day interval between each application.\n- Group 3: 17 horses to which both therapies (ozonized PRP and Shock Wave) were given with 10-day intervals between each treatment. All animals (regardless of the group to which they belonged) were subjected to the following\nworking protocol:\n? Day 1. Locomotor system assessment was done includins clinical and anesthetic blocks; In\naddition, the ultrasonographic evaluation was carried out on the same day. All the results\nobtained were recorded in forms and were randomly divided to form the different working groups. ? Day 2. first treatment that was assigned and then the 10 days interval between treatment and\ntreatment were respected. \n? 45 days after the last treatment, both clinically and ultrasound each treated animal was\nreassessed and the difference in the degree of pre- and post-treatment lactation was\ncompared and also the difference in the ultrasonographic image obtained after treatment\ncompared to the image obtained prior to them.\nThroughout the study, the horses lived in the respective stalls and perform daily health walks,\nin addition, they kept orthopedic hardware that in all cases was reconditioned every 30 days. The preparation of the PRP was carried out manually by the tube system and double\ncentrifugation, the activation was carried out by ozone treatment. Shock waves were applied locally over the lesion area. Fisher's Exact statistical method was used to analyze each of the\ntwo variables under study (claudication-ultrasonography). A p0?0.01 was considered\nsignificant. A total of 32 intralesional PRP Oz and 32 TOC have been applied without obtaining adverse\nreactions of any kind.\nFor the clinical variable (absence of lameness), with the use of PRP Oz a percentage of\n33.33% was obtained, 73.33% was obtained in the group that only received shock wave and\nfor the association of both therapies the percentage of absence of lameness was higher reaching a value of 94 ,12%. While for the ultrasound variable (enhancement in the ultrasound image) an improvement was observed in 66.67% for animals in group 1 (PRP Oz), a 46.65%\nimprovement for animals belonging to group 2 (TOC) and for the association of both treatments\nthe percentage of improvement was 88.24.\nDiscussion: The results of this study indicate an improvement in the rates evaluated when\ncomparing the evolutions of the animals that received both therapies associated with the indices obtained from the groups where the therapies were not associated. Compared to other studies, improvements are noted indisputable in terms of the type of regenerated tissue\nachieved and in terms of the improvement of clinical signs obtained without the use of\nanalgesics or anti-inflammatory drugs.\nConclusion: The results obtained showed that under these conditions, the use of both therapies in association is significantly more effective than if one or the other therapy is used\nindependently. Both therapies are safe and effective treatments in terms of relieving pain and\nstimulating the regeneration of scar tissue in the M. interosseus III of sports horses with proximal lesions of the aforementioned structure. The results obtained allow to recommend\nthe application of 3 doses of both associated therapies administered with intervals of 10 days.